SOCIALMEDIA USAGE, SELF-ESTEEM,AND LIFESATISFACTION AMONG SARAWAKTEENAGERS - Nur Shareena Azlin, Jefferia (Universiti Malaysia Sarawak (UNIMAS), 2021)
The purpose of this study is to investigate the relationship between social media usage, self - esteem, and life satisfaction among Sarawak teenagers using correlational study design. This study used quantitative survey method. A total number of 313 participants, from the areas including Kuching and Simanggang, Sarawak took part in this study. This study utilised three types of questionnaires, firstly the 10-item Social Networking Usage, secondly, the 6-item Rosenberg Self-Esteem Scale and lastly, 5-item Satisfaction With Life Scale. Originally, the Rosenberg Self-Esteem Scale consisted of 10 items. However, due to the low reliability and validity score of the test, four items were removed, leaving a total of six items to be used in this study. The data collected was analysed using the Statistical Package for Social Sciences (SPSS) Version 22. Pearson Correlation Coefficient was used to investigate the relationship between the variables, while Independent Sample T-test was used to investigate the relationship between the variables with gender. Majority of the hypothesis was rejected, and a small, positive correlation was found between self -esteem and life satisfaction among the Sarawak teenagers. As for future recommendations, future researchers are advised to conduct the similar study usingqualitative method,such asinterviewsto see if there are differencesin the findings.